Memory in Family: Theoretical Aspects and Insights from the Study on Past Regime’s Memory Transmission - Vervečkienė, Liucija (Politologija, 2022)
Difficult state-level questions of how to remember previous regimes are particularly linked with the „consumer“ side – specific areas of mnemonic socialization, such as families. A new generation raised during post-soviet transformations makes meaning of the recent past they have no direct or very limited experience of. This once again actualizes the questions of memory transmission within specific groups such as families initially analyzed in the case of memory of the crimes against humanity, mainly Holocaust. This article presents a theoretical overview of the factors to be kept mind in order to understand the remembering process within families: identification with the family memories, mnemonic socialization, loyalty relations, memory media and relation with the collective memory. Theoretical insights are supplemented by the empirical date of Lithuanian case (16 family conversations conducted in 2018–2020). Oldest members of the family still recall the begining of the previous regime, parents were raised in it whereas the third family generation was educated with a strong state emphasis on the previous regime as occupation and repressions-based period of the past. Those family experiences failing to fall into the category of a victim become uncomfortable. A shadow of collaboration imposed by the collective memory level leads to silencing or justification of those family memories.
Keywords: Memory; family; collective memory; communicative memory; previous regime; transmission